REALITAS KEKERASAN DAN PELECEHAN PEREMPUAN DI TEMPAT KERJA: ANALISIS PERSPEKTIF GENDER - Putri, Della First Tania; Wilodati, Wilodati; Wulandari, Puspita (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The amount of violence and harassment that women still experience in the workplace shows that there is no safe and comfortable place for women in the public environment, especially the workplace. The 2023 International Labour Organisation (ILO) Survey results also indicate that Indonesia is among the nations experiencing an emergency scenario of workplace violence. Based on this background, the research aims to shed light on the reality of workplace violence and harassment against women from a gender perspective. The literature review method was employed in this study. This approach uses numerous references from books, articles, and earlier research journals. This study used secondary data for its data collection. International journal databases like Google Scholar, Pubmed, Researchget, and Crossref were used for journal searches. The terms